Ethics vs. Prejudice: a challenge for professionals in leisure area - Silva, Renata Laudares; Schwartz, Gisele Maria (Journal of Physical Education (Maringá), 2008)
This qualitative research investigated the perception of prejudice against lesbianism in leisure activities, the motives for such individuals not to make public their sexual orientation and the leisure professional role as ethic posture disseminator during the inclusion process in leisure activities. A sample of 70 lesbians was interviewed via Internet and the data showed the existence of prejudice, fear of loosing social and familiar status and the professional fundamental participation for changing values in the inclusion process.